Automation Reporting Bed Efficiency Using Verification and Validation Method - Iis Gugum Gumilar; Yuda Syahidin; Erix Gunawan; Jeri Sukmawijaya (Universitas Bumigora, 2023)
Beds are important in several hospital operations decisions, such as admitting patients to a hospital room. Lack of information regarding bed effectiveness can lead to long wait times and even rejection of patients, which impedes hospital healthcare services, especially internal medicine departments Reside. The existence of an efficient system using an electronic bed is seen as a solution also makes the inpatient service process more efficient. It aims to create an electronic bed availability system that meets the needs of a hospital in Bandung city. This research using Qualiatif methods with verification and validationmodel as development method, called the verification and validation mode, was chosen because it is approriate for rapid system development. Resulted that easier to adjust as the hospital can contribute to the developing system. System information hospitalization indicator produce report about Bed Occupancy Rate, Length Of Stay, Turn Over Interval , and Bed Turn Over Interval bed availability, daily census, daily report, monthly report and all reporting. Based on the blackbox testing as s testing method, Reporting bed efficiency system developed has overcome information gap of bed availability at Hospital. Making processing and reporting more efficient and easier to use and understand